The Roman frontier with Persia in North-Eastern Mesopotamia : fortresses and roads around Singara - Comfort, Anthony, (Archaeopress Roman archaeology ;, 2023)
This volume investigates the Roman city of Singara and the fortifications and roads in the surrounding area. The Rome/Persia frontier has been little studied, in part because of the difficulty of access for scholars, but was of great importance because it separated the two major civilisations of the early first millennium CE.